Kant’s cosmopolitan interest in knowledge - Andaluz Romanillos, Ana María (Con-Textos Kantianos. International Journal of Philosophy, 2025)
This article draws attention to the problem of the meaning of knowledge in Kant and the need for an orientation of knowledge. In this perspective, it takes into consideration the kantian distinction between the scholastic concept of philosophy and the cosmic concept of philosophy. Isofar as this concept of philosophy defends the orientation of knowledge towards the moral ends or moral destiny of humanity, it is possible to speak of a cosmopolitan interest of knowledge. The thesis of the article is that this concept of philosophy is linked to the presence of the notion of the interest of reason in Kant, being, moreover, consistent with Habermas’s assessment of pure practical interest as a guiding interest of knowledge. It is structured in two points: 1. The interest of practical reason as a mobilising interest and a guiding interest of knowledge 2. The cosmic concept of philosophy as an expression of the cosmopolitan interest in and meaning of knowledge